REM Sleep Instability – A New Pathway for Insomnia? - Riemann, D.; Spiegelhalder, K.; Nissen, C.; Hirscher, V.; Baglioni, C.; Feige, B. (Pharmacopsychiatry, 2012)
Chronic insomnia afflicts approximately 10% of the adult population and is associated with daytime impairments and an elevated risk for developing somatic and mental disorders. Current pathophysiological models propose a persistent hyperarousal on the cognitive, emotional and physiological levels. However, the marked discrepancy between minor objective alterations in standard parameters of sleep continuity and the profound subjective impairment in patients with insomnia is unresolved. We propose that “instability” of REM sleep contributes to the experience of disrupted and non-restorative sleep and to the explanation of this discrepancy. This concept is based on evidence showing increased micro- and macro-arousals during REM sleep in insomnia patients. As REM sleep represents the most highly aroused brain state during sleep it seems particularly prone to fragmentation in individuals with persistent hyperarousal. The continuity hypothesis of dream production suggests that pre-sleep concerns of patients with insomnia, i. e., worries about poor sleep and its consequences, dominate their dream content. Enhanced arousal during REM sleep may render these wake-like cognitions more accessible to conscious perception, memory storage and morning recall, resulting in the experience of disrupted and non-restorative sleep. Furthermore, chronic fragmentation of REM sleep might lead to dysfunction in a ventral emotional neural network, including limbic and paralimbic areas that are specifically activated during REM sleep. This dysfunction, along with attenuated functioning in a dorsal executive neural network, including frontal and prefrontal areas, might contribute to emotional and cognitive alterations and an elevated risk of developing depression.
Keywords: insomnia; hyperarousal; REM sleep instability